1981
DOI: 10.1042/bj1950765
|View full text |Cite
|
Sign up to set email alerts
|

The role of the arginine-B22 residue in insulin action

Abstract: We describe the modification of the side chain of the arginine-B22 residue of insulin by. the N8N9-(1,2-dihydroxycyclohex-1,2-ylene) group and by the adipoyl group. These are the first insulin derivatives described that contain a modified arginine residue in an otherwise unaltered molecule. When tested for their ability to lower blood sugar concentration, both modified insulins showed a specific activity indistinguishable from that of insulin. In view of the fact that the substituent groups involved are very b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been reported that modification of R(B22) with a bulky group of the opposite charge does not alter the specific bioactivity of insulin ( 20 ) as in the case of R(B22)D substitution ( 21 ), which is naturally occurring in mole rats and guinea pigs ( 15 ). Similarly, the R(B22)E substitution has also been reported to retain insulin bioactivity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that modification of R(B22) with a bulky group of the opposite charge does not alter the specific bioactivity of insulin ( 20 ) as in the case of R(B22)D substitution ( 21 ), which is naturally occurring in mole rats and guinea pigs ( 15 ). Similarly, the R(B22)E substitution has also been reported to retain insulin bioactivity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proinsulin-R(B22)E (Fig. 1A) should lead to bioactive insulin (20)(21)(22), yet may not necessarily support efficient proinsulin protein folding (16; 26-29). We first examined the behavior of recombinant human proinsulin-R(B22)E. Min6 pancreatic β-cells express their own endogenous mouse proinsulin, but we probed transfected cells, and media, with an antibody that recognizes only human proinsulin protein.…”
Section: Expression Of Recombinant Proinsulin-r(b22)ementioning
confidence: 99%
“…It has been reported that modification of R(B22) with a bulky group of the opposite charge does not alter the specific bioactivity of insulin (20) as in the case of R(B22)D substitution (21), which is naturally occurring in mole rats and guinea pigs (15); similarly, the R(B22)E substitution has also been reported to retain insulin bioactivity (22). Here, we've pursued the possible impact of proinsulin-R(B22)E expression in the β-cells of mice in which this variant is knocked into the Ins2 locus.…”
Section: Introductionmentioning
confidence: 99%
“…The electrophoresis was performed on strips of cellulose acetate in a urea-containing borate buffer, pHa8.0, staining with Ponceau l, as described previously (Rose et al, 1981). FF indicates the position reached by the dye Cyanol FF, applied at the origin.…”
Section: Wsmentioning
confidence: 99%